Suppression of spring rain by surface greening over North China Plain - Xuezhen Zhang; Qiuhong Tang; Jingyun Zheng; Quansheng Ge; Rui Mao (International Journal of Climatology, 2015)
Surface greenness and rainfall in spring have changed from the 1980s to 1990s over the North China Plain (NCP). The greenness changes are characterized by large increase in north and little in south with an obvious greening zone from the centre of the NCP to the northeast. The rainfall change has a similar spatial pattern with reversed sign. The correlation between changes in greenness and rainfall is significant and the correlation ( r = −0.71, p